Penyuluhan Peningkatan Ekonomi Masyarakat Melalui Pengembangan Potensi Desa di Desa Pantai Labu, Kabupaten Deli Serdang - Daulay, Muhammad Syafii Murad; Hasanah, Uswatun; Yunita, Mella; Yudhira, Ahmad; Lubis, Hilman; Paryogi , Oki (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This outreach program aims to boost the local economy in Pantai Labu Village by developing the potential of its residents as traders. It focuses on enhancing their trading skills, marketing, and business management through participatory approaches that involve the local community in the outreach process, including providing guidance in managing their trading ventures. Research results have shown a significant improvement in the economic well-being of Pantai Labu Village residents who participated in the outreach program. Traders who received training and guidance managed to increase their income. Furthermore, the formation of business groups also facilitated collaboration among traders and joint marketing efforts, enhancing their competitiveness in the local market. Through a participatory approach and appropriate training, the community can improve their trading skills and knowledge, thereby optimizing the local economic potential. This also encourages collaboration and joint marketing, which has a positive impact on trader income and the overall village economy.